MENGAWINKAN PAIKEM DAN MODEL KREATIF-PRODUKTIF DALAM PEMBELAJARAN MENULIS KREATIF PUISI - Sudaryono . (Program Studi Pendidikan Bahasa dan Sastra Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2012)
Teaching experiences change of paradigm along with development of teaching model. Recently, introduced active inovatif creative effective and pleases teaching (AICEPT). Before all, introduced teaching model of creative producktive (TMCP) in study literary. This article is presentation of implementation effort reality of recent teaching model for study writes creative of poem. This study base is creativity, sensitivity, and instructor initiative allied with ideal study model that its. Keywords: writes creative of poem, strategy AICEPT, TMCP